Method for resolution and quantification of components of the non-photochemical quenching (q (N)) - Roháček, Karel (Photosynthesis research, 2010)
A new method of the chlorophyll (Chl) a fluorescence quenching analysis is described, which allows the calculation of values of (at least) three components of the non-photochemical quenching of the variable Chl a fluorescence (q (N)) using a non-linear regression of a multi-exponential function within experimental data. Formulae for coefficients of the "energy"-dependent (DeltapH-dependent) quenching (q (E)), the state-transition quenching (q (T)) and the photo/inhibitory quenching (q (I)) of Chl a fluorescence were found on the basis of three assumptions: (i) the dark relaxation kinetics of q (N), as well as of all its components, is of an exponential nature, (ii) the superposition principle is valid for individual Chl a fluorescence quenching processes and (iii) the same reference fluorescence level (namely the maximum variable Chl a fluorescence yield in the dark-adapted state, F (V)) is used to define both q (N) and its components. All definitions as well as the algorithms for analytical recognition of the q (N) components are theoretically clarified and experimentally tested. The described theory results in a rather simple equation allowing to compute values for all q (N) components (q (E), q (T), q (I)) as well as the half-times of relaxation (tau(1/2)) of corresponding quenching processes. It is demonstrated that under the above assumptions it holds: q (N) = q (E) + q (T) + q (I). The theoretically derived equations are tested, and the results obtained are discussed for non-stressed and stressed photosynthetically active samples. Semi-empirical formulae for a fast estimation of values of the q (N) components from experimental data are also given.
Keywords: Plant Leaves; kukuřice setá; regresní analýza; Time Factors; tma; fluorescence; fazol; listy rostlin; časové faktory; Kinetics; chlorofyl; Regression Analysis; fotochemie; kinetika; Photochemistry; Phaseolus; Zea mays; Fluorescence; Darkness; Chlorophyll